Self-Efficacy and Job Motivation as Determinants of Performance of Library Staff in Southwest Universities, Nigeria - Oyetunji, Temitope Kehinde; Abdulwahab, Issa Issa; Eromosele, George Osas (Insaniyat : Journal of Islam and Humanities, 2024)
This study examined self-efficacy and job motivation as determinants of the performance of library staff in universities in Southwest Nigeria. The study adopted a descriptive survey design, and a sample of 180 library staff was selected across the three selected university libraries using a total enumeration sampling technique. A questionnaire was used to collect data from 180 respondents, out of which 176 copies of the questionnaire were returned and found usable for the analysis. Descriptive statistics (frequency counts, simple percentages) were used to analyze data on the six research questions, while inferential statistics (multiple regression) was used to test the null hypothesis. The study found that the performance of library staff in the selected university libraries was high, even as they held a positive opinion about themselves. Wages and salary, appreciation, promotion, benefits, and allowances were the major factors that motivated them to perform their jobs. Self-efficacy and job motivation significantly influenced their performance. The findings also revealed that unwillingness by library authorities to train staff for the future, inadequate funding to support career development programs, poor organizational climate in the library, lack of complete senior management commitment and support, and uncertainty of library staff about the future of their career were the major barriers that affected their job performance. The study established that the combination of self-efficacy and job motivation did not jointly determine the library staff performance. The study recommended that library staff should be adequately motivated continually to boost their morale for efficiency and higher productivity.